Child catastrophizing about parent chronic pain: A potential child vulnerability factor. Issue 2 (20th March 2020) - Higgins, Kristen S.; Chambers, Christine T.; Rosen, Natalie O.; Sherry, Simon; Mohammadi, Somayyeh; Lynch, Mary E.; Campbell‐Yeo, Marsha; Clark, Alexander J.
Abstract : Objective: Robust evidence suggests children's catastrophizing about their own pain is a risk factor for poor child pain‐related outcomes. In children of parents with chronic pain, child catastrophizing about their parents' pain might be a unique predictor of child pain‐related outcomes given their increased exposure to parental chronic pain and disability. The objective of this study was to examine associations between child and parent catastrophizing about their own and each other's pain and child and parent pain‐related outcomes. Methods: Seventy‐two parents with chronic pain and their children (ages 8–15) completed questionnaires assessing their trait catastrophizing about their own and each other's pain, their own pain, and the child's internalizing symptoms. Children completed the cold pressor task (CPT) in the presence of their parent. Parents and children rated children's worst pain intensity and their own anxiety during the task. Analyses were guided by the Actor‐Partner Interdependence Model. Results: Greater child catastrophizing about parent pain was associated with children's and parents' increased catastrophizing about their own pain. Child catastrophizing about parent pain was associated with greater child‐ and parent‐reported child internalizing symptoms and greater CPT pain intensity for the child, but not parent/child usual pain or CPT anxiety, over and above the influence of parent and child catastrophizing about their own pain. Conclusions: Child catastrophizing about parent pain is a potential vulnerability factor associated with poor pain‐related outcomes in children of parents with chronic pain that should be considered in future research and clinical settings. Statement of contribution What is already known on this subject? Higher rates of pain and internalizing symptoms are observed in offspring of parents with vs. without chronic pain. Greater child and parent pain catastrophizing are associated with poorer pain‐related outcomes in children. Child catastrophizing about parent chronic pain and its association with child outcomes has not been examined. What does this study add? Greater child catastrophizing about parent chronic pain is associated with greater child internalizing and CPT pain. These effects were seen beyond the association of child and parent catastrophizing about their own pain.